Endoscopic submucosal dissection for early esophageal cancer associated with achalasia - Yu OHKURA; Toshiro IIZUKA; Daisuke KIKUCHI; Satoshi YAMASHITA; Masanori NAKAMURA; Akira MATSUI; Toshifumi MITANI; Shu HOTEYA; Mitsuru KAISE; Naohisa YAHAGI (Turkish Journal of Gastroenterology, 2019)
-